2018
DOI: 10.1128/aac.00404-18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Analysis of mcr-3 -Positive Aeromonas Species from Humans, Retail Meat, and Environmental Water Samples

Abstract: The mobile colistin resistance gene is globally disseminated in both and species, with the latter potentially serving as a reservoir for this gene. Here, we investigated the prevalence of in rectal swabs from humans, in food-producing animals and their products, and in the aquatic environment, and we investigated the genetic relationships between the -positive isolates. An enriched broth screening method was used to detect in samples, and species identification of isolates from positive samples was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 28 publications
6
70
1
Order By: Relevance
“…have been reported and widely isolated from humans, retail meat and environmental water (Shen et al ., ). Most of these mcr‐3‐ positive strains showed moderate susceptibility to colistin and failed in transconjugation of mcr‐3 gene variants to E. coli recipients (Shen et al ., ), consistent with our findings that mcr‐3 variants are located on a prophage. Thus, Aeromonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…have been reported and widely isolated from humans, retail meat and environmental water (Shen et al ., ). Most of these mcr‐3‐ positive strains showed moderate susceptibility to colistin and failed in transconjugation of mcr‐3 gene variants to E. coli recipients (Shen et al ., ), consistent with our findings that mcr‐3 variants are located on a prophage. Thus, Aeromonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…15,24 Until now, there are several mcr-3 variants, including mcr-3.3 and mcr-3.13 to mcr-3.18, identified among 10 Aeromonas isolates from different sources. 12 Shen et al reported samples from the aquatic environment had the highest prevalence (10.0%) of mcr-3-positive Aeromonas isolates, 12 which indicated that mcr-3 have been disseminated throughout various environments, the aquatic environment might be the major reservoir. For this study, it is the first case about a novel transposon, Tn6518, mediated transfer of mcr-3.6 in ESBL-producing Aeromonas veronii isolated from chicken faeces.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Subsequently, multiple mcr-3 variants and one mcr-5 gene were identified in Aeromonas species, implying Aeromonas species plays an important role in the dissemination of mobile colistin resistance genes. [11][12][13] Among them mcr-3 was first found in Escherichia coli isolated from pig, 14 then some papers illustrated that this gene emerged in Aeromonas spp. 12 Subsequently, Ling et al study showed that mcr-3.3 and mcr-3-like have emerged in Aeromonas veronii isolated from retail chicken meat, 8 and Eichhorn et al found four Aeromonas isolates were positive for mcr-3, each of the four mcr-3 genes showed amino acid identities of 95.0-98.0% to the original mcr-3 protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that Aeromonas can survive at pH = 5 [14,130]. Many studies have investigated the incidence of Aeromonas in meat products [128,131,132]. Based on the sequencing of HKG like rpoD and gyrB, the most prevalent species were A. veronii, A. salmonicida, A. jandaei, A. simiae, A. hydrophila, and A. caviae [81,125].…”
Section: Aeromonas In Foodmentioning
confidence: 99%